2017
DOI: 10.1038/s41598-017-09754-5
|View full text |Cite
|
Sign up to set email alerts
|

Linc-ing Circulating Long Non-coding RNAs to the Diagnosis and Malignant Prediction of Intraductal Papillary Mucinous Neoplasms of the Pancreas

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is an aggressive disease that lacks effective biomarkers for early detection. We hypothesized that circulating long non-coding RNAs (lncRNAs) may act as diagnostic markers of incidentally-detected cystic PDAC precursors known as intraductal papillary mucinous neoplasms (IPMNs) and predictors of their pathology/histological classification. Using NanoString nCounter® technology, we measured the abundance of 28 candidate lncRNAs in pre-operative plasma from a cohort of path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 76 publications
2
52
0
Order By: Relevance
“…28,29,78 Lower expression of GAS5 in plasma was found in intraductal papillary mucinous neoplasms (IPMNs) compared to non-diseased controls, suggesting that a GAS5-based blood test may be used as an adjunct diagnostic tool for identifying IPMNs. 79 Thus, GAS5 may be used as a potential biomarker for diagnosis in patients with PC. Ovarian cancer (OC) is one of the most common gynecological malignancies in the world with low 5-year OS.…”
Section: Clinical Relevancementioning
confidence: 99%
“…28,29,78 Lower expression of GAS5 in plasma was found in intraductal papillary mucinous neoplasms (IPMNs) compared to non-diseased controls, suggesting that a GAS5-based blood test may be used as an adjunct diagnostic tool for identifying IPMNs. 79 Thus, GAS5 may be used as a potential biomarker for diagnosis in patients with PC. Ovarian cancer (OC) is one of the most common gynecological malignancies in the world with low 5-year OS.…”
Section: Clinical Relevancementioning
confidence: 99%
“…The sensitivity was 81% with a specificity of 53%. In another study by the same research group, it was shown that 8 lncRNAs (ADARB2-AS1, ANRIL, GLIS3-AS1, LINC00472, MEG3, PANDA, PVT1 and UCA1) could predict malignant IPMN (high-grade dysplasia or invasive carcinoma) with a sensitivity of 77% and specificity of 76% [17]. When the lncRNA panel was combined with the miRNA data, radiomic data and standard clinical and radiologic features, the accuracy of predicting IPMN grade could be improved, yielding a sensitivity of 93% and specificity of 82% with an AUC of 0.92.…”
Section: Editorialmentioning
confidence: 98%
“…Another mechanism of target gene regulation is achieved by binding to chromatin complexes or causing histone epigenetic modifications, which is the case for the lncRNA HOTAIR [4]. LincRNAs may act as enhancers and actively regulate the transcription of proximal genes [26].…”
Section: Lncrna Classification and Functionmentioning
confidence: 99%
“…Other reports have shown that GAS5 contributes to drug-induced apoptosis through PTEN regulation by miR-32-5p in different PC cell lines [87]. Jennifer et al successfully quantified 28 lncRNA mutants in preoperative archived plasma from a cohort of pathologically confirmed intraductal papillary mucinous neoplasm (IPMN) cases and unaffected controls [26]. Their results showed that GAS5 could differentiate IPMN samples from healthy samples.…”
Section: Gas5mentioning
confidence: 99%